2003
DOI: 10.1007/s00018-003-2290-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and the regulation of fat reserves

Abstract: Beyond their classical nutritional roles, nutrients modify gene expression and function in target cells and, by so doing, affect many fundamental biological processes. An emerging example, which is the focus of this review, is the involvement of vitamin A in the regulation of the level and functioning of body fat reserves. Retinoic acid, the carboxylic acid form of vitamin A, is a transcriptional activator of the genes encoding uncoupling proteins, and results in animals indicate that whole body thermogenic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 80 publications
4
125
1
4
Order By: Relevance
“…This induction is explained by the existence of RA and PPAR response elements in the UCP1 gene promoter. Induction of other UCP family members by all-trans RA has also been reported (see [6]). …”
Section: Adipocyte Differentiationmentioning
confidence: 82%
See 3 more Smart Citations
“…This induction is explained by the existence of RA and PPAR response elements in the UCP1 gene promoter. Induction of other UCP family members by all-trans RA has also been reported (see [6]). …”
Section: Adipocyte Differentiationmentioning
confidence: 82%
“…Bovine marbling (which is the presence of a high amount of fat in muscle) is enhanced in the cattle by diets low in carotenoids, so that marbling development is inversely correlated with serum vitamin A levels [39]. In rodents, the administration of RA (reviewed in [6]) or retinal [85] reduces body weight and body fat, and increases insulin sensitivity. Long-term vitamin A supplementation (as retinyl palmitate) has been shown to associate with a mild reduction of adiposity in rats [41] and has certain counterbalancing effect on the development of diet-induced obesity in mice [15].…”
Section: Carotenoid/retinoid Pathway and Lipid Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, D'Souza et al (2003) reported higher IMF content (153%) in pigs fed grower and finisher diets deficient in vitamin A. It has been proposed that the effect of vitamin A on IMF deposition is mediated by retinoic acid, a derivative of vitamin A that inhibits adipocyte differentiation both in vivo and in vitro (Sato et al, 1980;Bonet et al, 2003). Therefore, vitamin A restriction is supposed to increase hyperplasia (Gorocica-Buenfil et al, 2007).…”
Section: Manipulating Dietary Protein Energy and Micronutrientsmentioning
confidence: 99%